2017
DOI: 10.1186/s12891-017-1639-5
|View full text |Cite
|
Sign up to set email alerts
|

HLA B27 antigen in Middle Eastern and Arab countries: systematic review of the strength of association with axial spondyloarthritis and methodological gaps

Abstract: BackgroundAxial spondyloarthritis (AxSpA) is a relatively frequent and debilitating disease, with a prevalence ranging from 0.1 to 2% in the Caucasian population. Current Assessment of Spondyloarthritis International Society (ASAS) classification criteria of AxSpA rely either on sacroiliitis on imaging plus one SpA feature or positive HLAB27 antigen plus two SpA features, in a patient with chronic low back pain and age at onset of less than 45 years. Therefore, HLA-B27 is a central feature in SpA classificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 35 publications
5
48
0
Order By: Relevance
“…Our study confirmed the lower prevalence of HLA‐B27 in axSpA patients (41.1%) and BD participants (3.8%) in Lebanon, compared to northern populations . These results are in line with the prevalence found in normal populations from the Arab and Middle Eastern region (0.3%‐6.8%) but are still lower than the published prevalences for axSpA (42.7%‐84%) …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our study confirmed the lower prevalence of HLA‐B27 in axSpA patients (41.1%) and BD participants (3.8%) in Lebanon, compared to northern populations . These results are in line with the prevalence found in normal populations from the Arab and Middle Eastern region (0.3%‐6.8%) but are still lower than the published prevalences for axSpA (42.7%‐84%) …”
Section: Discussionsupporting
confidence: 90%
“…It is a class I antigen of the major histocompatibility complex that is present in 6%‐8% of the general population and in 80%‐95% of AS patients in western European and North American populations . However, the prevalence of HLA‐B27 in axSpA patients is found to be lower in Japan and in most Arab and Middle Eastern populations, compared to western European populations, possibly due to different genetic backgrounds . The lowest figures in the region were found in Lebanon with a prevalence of 26.3% in AS, 13.8% in SpA and 1.4% in the general population, according to the latest published study in 1997 .…”
Section: Introductionmentioning
confidence: 99%
“…The positivity rate of HLA-B27 in patients with AS has been reported at 72% [13], 73% [23], 74.8% [31], and 76.2% [32], which are close to that reported in the present study. These percentages are significantly higher than the rate of HLA-B27 positivity in the general population in Iran (less than 4%) [33,34]. HLA-B27 is the strongest genetic factor associated with AS and AAU, and a higher prevalence of AAU [28] and more severe SpA is observed in HLA-B27 positive patients [35].…”
Section: Discussionmentioning
confidence: 95%
“…The most important limitation is the small number of patients which makes precise generalized conclusions potentially arguable. Nonetheless, AS may be even rarer in the Middle Eastern and Arab countries [32]. A longitudinal study with further indepth analysis is recommended to verify the reached findings, to determine the response to medications, detect the disease outcome and any confounding factors.…”
Section: Short Communicationmentioning
confidence: 98%